2003
DOI: 10.1021/jf0304324
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Extracts, Condensed Tannin Fractions, and Pure Flavonoids from Phaseolus vulgaris L. Seed Coat Color Genotypes

Abstract: Twelve different seed coat color genotypes of Phaseolus vulgaris L. were extracted and pure flavonoids isolated from 10 of these. The seed coat methanol extracts, tannin fractions, and pure flavonoids all displayed antioxidant activity in a fluorescence-based liposome assay. The relatively high activity of the condensed tannin (proanthocyanidin) fractions indicates that these may play an important role in the overall activity of the extracts. This activity also indicates that although these polyphenols cause p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
178
3
12

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(209 citation statements)
references
References 26 publications
10
178
3
12
Order By: Relevance
“…The same finding was reported in the study by Beninger and Hosfield [14], who explained their results by noting that the flavonoids present in the crude extract were further concentrated in the extracts; this concentration may have been primarily responsible for the observed antioxidant activity.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The same finding was reported in the study by Beninger and Hosfield [14], who explained their results by noting that the flavonoids present in the crude extract were further concentrated in the extracts; this concentration may have been primarily responsible for the observed antioxidant activity.…”
Section: Discussionsupporting
confidence: 85%
“…Although Beninger and Hosflied [14] indicated that flavonoids exist mainly in the glycosylated form, the fractions evaluated in this study also contained the aglycone flavonoid.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The order of the sugars cannot be determined by LC-DAD-ESI/MS, since the mass spectra did not offer any fragments to indicate the mass of the secondary sugar. Both sugar orders, kaempferol 3-O-glucosylxylose in Montcalm dark kidney beans seed coats (Beninger & Hosfield, 2003;Beninger & Hosfield, 1999) and keampferol 3-Oxylosylglucoside in the Zolfino common bean landraces (P. vulgaris L., cv. Zolfino) (Romani et al, 2004), have been reported.…”
Section: Identification Of Bean Flavonoidsmentioning
confidence: 99%
“…There are 10 major US commercial market classes of dry beans: black beans (Aparicio-Fernades et al, 2006;Aparicio-Fernandez, Yousef, Loarca-Pina, Gonzales de Mejia, & Lila, 2005;Takeoka et al, 1997), pinto beans (Beninger et al, 2005;Beninger & Hosfield, 2003), light and dark red kidney beans (Beninger & Hosfield, 1999;Choung, Choi, An, Chu, & Cho, 2003), pink beans, navy beans, great northern beans (Kelly et al, 2003;Luthria & Pastor-Corrales, 2006), alubia beans (Kelly & Copeland, 1998;Kelly, Hosfield, Varner, Uebersax, & Taylor, 1999) cranberry beans (Beaver, 1999), and small red beans, also known as redMexican beans (Hosfield, Varner, Uebersax,& Kelly, 2004). Common dry beans contain a wide range of flavonoids, including flavonols, their glycosides, anthocyanins, proanthocyanidins, and isoflavones, as well as some phenolic acids (Aparicio-Fernades & Garica-Gasca et al, 2006;Aparicio-Fernades & Yousef et al, 2005;Beninger & Hosfield, 1999;Beninger & Hosfield, 2003;Choung et al, 2003;Diaz-Batalla, Widholm, Fahey, Casano-Tostado, & Paredes-López, 2006;Macz-Pop, González-Parama´s, Pérez-Alonso, & Rivas-Gonzalo, 2006;Romani et al, 2004;Takeoka et al, 1997) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%